A Case Study of a Low Power Vapour Adsorption Refrigeration System. (September 2016) - Dinesh, Banala; Sai Manikanta, M.; Dishal Kumar, T.; Sahu, Debjyoti
Abstract: Industrial refrigeration is one of the most energy consuming sector. In conventional Vapor Compression refrigeration system, compressor is the major power consuming element. Vapor Adsorption refrigeration system is one of the best replacement for the Vapor Compression refrigeration system. Our main objective is to analyze, design and develop a Vapor Adsorption refrigeration system which is cost effective and environmental friendly. A prototype model that is capable of producing a temperature drop in closed evaporator chamber was designed, fabricated and tested. Activated carbon/Methanol pair is chosen as Adsorbent/Refrigerant pair. The system is analyzed in ANSYS 14.5 using the inlet conditions obtained from the experimental setup. The performances and effectiveness of the unit was studied by determining Refrigeration Effect (RE), Coefficient of Performance (COP) and explaining operational issues of the unit. The results obtained from the analysis and experiments have marginal difference in COP i.e. with an error percentage of 5.94%. The overall COP obtained is 0.34 through experiments and from analysis the COP obtained is approximately 0.32.